Sectoral Stock Pricing in the Nigerian Stock Exchange: Symmetric and Asymmetric Approaches (Journal of Management and Social Sciences, 2026)
Each sector has a symbolic pattern that predicts the likelihood of returns. This study investigates sectoral stock price volatility at the Nigerian Exchange Group. The volatility dynamics of sectoral stock returns under symmetric and asymmetric conditions using the data on selected exogenous variables such as consumer price index, Treasury bill rate, and market price of stocks and monthly firm stock price categorised into each sector were investigated using the Traditional GARCH, Threshold GARCH, and Exponential GARCH models. Apart from GARCH models, it was used to establish the relationships among the determinants of expected returns. Arising from the pricing purpose, some sectors were overvalued (Agriculture, Conglomerate, Construction, Consumer goods, Health, Oil & Gas, and Services) while others (Financial Services and Natural Resources) were undervalued. However, volatility in most sectoral stock returns is not permanent but rather mean-reverting, and they perform much better under the leverage effect, implying that negative news (shocks) has more influence on stock price volatility than positive news. Meanwhile, it remains a fact that volatility is not relevant in determining expected returns after estimating and applying asset pricing models. Hence, the study provides evidence in favour of a portfolio of sectoral stocks as a more beneficial investment strategy than aggregate stock market indices, thereby supporting portfolio theory. The study then recommends that the government, through its agencies, should mobilise adequate funds into the market to stabilise it during periods of high volatility, as well as improve stock market education to mitigate the effects of negative news, while investors should improve their knowledge of each sector for portfolio management.KeywordsStock returns, volatilities, asset pricing, GARCH, TGARCH, EGARCH, ARDL, Nigerian Stock Exchange